Optimal Extracellular Matrix Niches for Neurogenesis: Identifying Glycosaminoglycan Chain Composition in the Subventricular Neurogenic Zone - Kerever, Aurelien; Arikawa-Hirasawa, Eri (Frontiers in Neuroanatomy, 2021)
n the adult mammalian brain, new neurons are generated in a restricted region called the neurogenic niche, which refers to the specific regulatory microenvironment of neural stem cells. Among the constituents of neurogenic niches, the extracellular matrix (ECM) has emerged as a key player in neural stem cell maintenance, proliferation, and differentiation. In particular, heparan sulfate proteoglycans are capable of regulating various growth factor signaling pathways that influence neurogenesis. In this review, we summarize our current understanding of the ECM niche in the adult subventricular zone, with a special focus on basement membrane-like structures called fractones. We also discuss how fractones, particularly their composition of glycosaminoglycans, may influence neurogenesis